2013
DOI: 10.1103/physrevlett.110.213201
|View full text |Cite
|
Sign up to set email alerts
|

Electron- and Proton-Impact Excitation of Hydrogenlike Uranium in Relativistic Collisions

Abstract: The K shell excitation of H-like uranium (U(91+)) in relativistic collisions with different gaseous targets has been studied at the experimental storage ring at GSI Darmstadt. By performing measurements with different targets as well as with different collision energies, we were able to observe for the first time the effect of electron-impact excitation (EIE) process in the heaviest hydrogenlike ion. The large fine-structure splitting in H-like uranium allowed us to unambiguously resolve excitation into differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 29 publications
5
30
1
Order By: Relevance
“…For instance, the resonance strengths of DR into highly charged heavy ions are greatly enhanced by the Breit interaction, as shown in our previous work [26] and also by Bernhardt et al [27]. The Breit interaction also plays an important role in the quantum interference between resonant DR and nonresonant radiative recombination (RR) processes [28,29] as well as electron-impact excitation [30,31] and ionization [32,33].…”
Section: Introductionsupporting
confidence: 58%
“…For instance, the resonance strengths of DR into highly charged heavy ions are greatly enhanced by the Breit interaction, as shown in our previous work [26] and also by Bernhardt et al [27]. The Breit interaction also plays an important role in the quantum interference between resonant DR and nonresonant radiative recombination (RR) processes [28,29] as well as electron-impact excitation [30,31] and ionization [32,33].…”
Section: Introductionsupporting
confidence: 58%
“…For example, this was necessary in the polarization of x rays emitted during electron-impact excitation of highly charged ions [1,2], dielectronic and radiative recombination effects [3][4][5], electron-impact-ionization experiments [6][7][8], and electron-and proton-impact excitation experiments [9]. For electron-impact excitation of highly charged hydrogenlike ions, Walker [10], Fontes et al [11], and Moores and Pindzola [12] have demonstrated that the Møller interaction or GBI can increase electron-impact-excitation cross sections by up to 50% in comparison to calculations that employ only the Coulomb interaction.…”
Section: Introductionmentioning
confidence: 99%
“…A pplication o f the C om pton polarim etry technique provides a significant advantage over the Bragg polarim etry technique, previously used at EBITs [17,48,[72][73][74], by m easuring, in addition to the degree o f polarization, the angle o f polariza tion [42,61 ] and by being effective in a broader range o f ener gies [41,75], O ur im plem entation o f the C om pton polarim etry is also significantly more accurate [26,41,42,60,61,76] than a sim ilar techniques used in nuclear physics [77][78][79][80], The high polarim etry accuracy allows deep probes o f the electronim pact ionization and excitation [48,[72][73][74]81,82], resonant excitation [83], and radiative recom bination [26,51,84] by revealing the alignm ent [51,84,85] …”
Section: Resultsmentioning
confidence: 99%